2017
DOI: 10.3847/1538-3881/aa6572
|View full text |Cite
|
Sign up to set email alerts
|

KELT-11b: A Highly Inflated Sub-Saturn Exoplanet Transiting the V = 8 Subgiant HD 93396

Abstract: We report the discovery of a transiting exoplanet, KELT-11b, orbiting the bright (V = 8.0) subgiant HD 93396. A global analysis of the system shows that the host star is an evolved subgiant star with T eff = 5370±51 K, M * = 1.438−0.046 , and [Fe/H]= 0.180 ± 0.075. The planet is a low-mass gas giant in a P = 4.736529 ± 0.00006 day orbit, with M P = 0.195 ± 0.018 M J , R P = 1.37, surface gravity log g P = 2.407−0.086 , and equilibrium temperature T eq = 1712 +51 −46 K. KELT-11 is the brightest known transiting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 82 publications
(103 reference statements)
5
45
0
Order By: Relevance
“…The spacecraft's four year primary mission, together with its more recent K2 program extension (Howell et al 2014), confirmed the existence of over 2500 planets 1 , including many that resemble nothing found in the solar system. This incredible diversity includes the so-called 'hot Jupiters' and 'hot Neptunes' (e.g., Mayor & Queloz 1995;Charbonneau et al 2000;Gillon et al 2007;Bakos et al 2010;Bayliss et al 2013), planets moving on extremely eccentric orbits (e.g., Jones et al 2006;Wittenmyer et al 2017), planets with densities greater than iron and even osmium (e.g., Deleuil et al 2008;Dumusque et al 2014;Johns et al 2018), or comparable to styrofoam (e.g., Faedi et al 2011;Welsh et al 2015;Pepper et al 2017). Perhaps most surprisingly, Kepler revealed that planets between the size of Earth and Neptune ("super-Earths" or "mini-Neptunes") are incredibly common, despite the fact that no analog exists in the solar system (e.g., Charbonneau et al 2009; Barragán et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The spacecraft's four year primary mission, together with its more recent K2 program extension (Howell et al 2014), confirmed the existence of over 2500 planets 1 , including many that resemble nothing found in the solar system. This incredible diversity includes the so-called 'hot Jupiters' and 'hot Neptunes' (e.g., Mayor & Queloz 1995;Charbonneau et al 2000;Gillon et al 2007;Bakos et al 2010;Bayliss et al 2013), planets moving on extremely eccentric orbits (e.g., Jones et al 2006;Wittenmyer et al 2017), planets with densities greater than iron and even osmium (e.g., Deleuil et al 2008;Dumusque et al 2014;Johns et al 2018), or comparable to styrofoam (e.g., Faedi et al 2011;Welsh et al 2015;Pepper et al 2017). Perhaps most surprisingly, Kepler revealed that planets between the size of Earth and Neptune ("super-Earths" or "mini-Neptunes") are incredibly common, despite the fact that no analog exists in the solar system (e.g., Charbonneau et al 2009; Barragán et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…KELT observations have surveyed more than 70% of the celestial sphere, down to a limiting magnitude near V ∼ 13, with a baseline of 9 yrs using KELT North (hereafter, KELT-N) and 5 yrs using KELT South (hereafter, KELT-S). Initially deployed to detect exoplanet transits around bright (V < 10) stars, the survey has contributed discoveries to supernovae (Siverd et al 2015), the monitoring of Be Stars (Labadie-Bartz et al 2017), eclipses of stars by disks (Rodriguez et al 2013), gyrochronology of young stars (Cargile et al 2014), pre-identification of young variable objects to be observed by K2 (Rodriguez et al 2017a,b;Ansdell et al 2017), more than 21 confirmed transiting planets (with 19 in press Pepper et al 2013;Collins et al 2014;Bieryla et al 2015;Fulton et al 2015;Eastman et al 2016;Kuhn et al 2016;Rodriguez et al 2016c;Zhou et al 2016;Gaudi et al 2017;McLeod et al 2017;Oberst et al 2017;Pepper et al 2017;Stevens et al 2017;Temple et al 2017;Lund et al 2017;Siverd et al 2017)) and 1 short period, transiting brown dwarf .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several papers have provided multiple lines of evidence showing that the initial spectroscopic estimates of the masses of the "Retired A Stars" were likely generally slightly overestimated and the uncertainties in their masses likely underestimated. Indeed, it appears that the majority of the members of the "Retired A Star" sample that have accurate mass measurements (via astroseismology or transits; Johnson et al 2014;Pepper et al 2017;Campante et al 2017;North et al 2017;Stassun et al 2017;Stello et al 2017) appear to actually be "Retired F Stars," i.e., more massive than the solar-type stars that dominated early RV surveys (and are therefore more massive than the Kraft break), but less massive than a zero-age main-sequence (ZAMS) A star. In retrospect, this fact should not be very surprising, as the average age of the Galactic thin disk (whose stars dominate the local solar neighborhood) is 7.4 8.2 Gyr - (Kilic et al 2017), corresponding to the hydrogen-fusing lifetime of a ZAMS late F star.…”
Section: Introductionmentioning
confidence: 99%